Feeding practices, nutrition and gastro-oesophageal reflux disease (GORD) among newborn infants in neonatal units - Abdul Hamid, Haslina (2022)
With improved care, infants born preterm are likely to survive both in high and low-resource settings. However, rate of postnatal growth failure is known to be high around the world although studies in Southeast Asia are still lacking. Effective interventions are needed to ensure that preterm infants can grow optimally. Nutrition, as one of the most important aspects in the postnatal care of preterm infants should be the top priority. Application of feeding practices varies, due to the differing protocols in neonatal units and medical conditions of the infants. In my first study (Chapter 2), nutritional practices and intakes among preterm infants in the neonatal units in Malaysia and the UK are compared and the association with growth at discharge was analysed. Results have shown that a higher number of Malaysian infants received breast milk (Malaysia: 98%, UK: 76%, p=0.001) and parenteral nutrition (Malaysia: 80%, UK: 38%, p<0.001) during admission. Malaysian infants received more protein (3.0 vs 2.7g, p=0.004) and had fewer energy and protein deficits (-191.6 kcal/kg vs -254.5 kcal/kg, -11.4 g/kg vs -15.4 g/kg) on week 1-4 of life as compared to infants in the UK unit. Despite this, more than half of infants in both units were discharged with growth failure, defined as a change in weight-for-age Z-score (WAZ) of >-1.28. Infants who had a longer length of stay had a larger drop in WAZ in the Malaysia unit. This relationship was not found in the UK cohort where protein intake and protein energy ratio (PER) were the variable that associated with changes in WAZ between birth and discharge.